Usage Pattern of Carbamazepine and Associated Severe Cutaneous Adverse Reactions in Singapore Following Implementation of HLA-B*15:02 Genotyping as Standard-of-Care - Sung, Cynthia; Tan, Liesbet; Limenta, Michael; Ganesan, Ganga; Toh, Dorothy; Chan, Cheng Leng (Frontiers in Pharmacology, 2020)
In April 2013, the Ministry of Health and Health Sciences Authority of Singapore jointly issued recommendations for HLA-B*15:02 genotyping before starting carbamazepine (CBZ) in new patients of Asian ancestry as standard of care. The Ministry of Health also approved a 75% subsidy for HLA-B*15:02 genotyping to all patients on subsidy at public healthcare institutions. To understand the impact of these regulatory decisions, we researched the usage patterns for CBZ and levetiracetam, the trend of Stevens–Johnson syndrome/toxic epidermal necrolysis [Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN)] reports associated with antiepileptic drugs and the take-up rates of HLA-B*15:02 tests in Singapore. In the 5-year post-policy period, we found that the annual number of reported SJS/TEN cases associated with all antiepileptic drugs was significantly decreased by 57% (p = 0.015); SJS/TEN cases associated with CBZ and phenytoin reduced by 92% and 42% respectively. New CBZ users decreased by 31% while new levetiracetam users approximately doubled. The annual number of HLA-B*15:02 tests conducted increased from 444 to approximately 1,200. Regulatory recommendations for HLA-B*15:02 genotyping as standard of care coupled with government subsidy for the test had contributed to a reduction in CBZ SJS/TEN in Singapore by >90%, in line with that observed in other Asian countries with similar policies. Additionally, the number of phenytoin-SJS/TEN cases also declined. Taken together, this represents a successful example of precision medicine through implementation of a genotyping program to reduce a rare but serious adverse drug reaction among at-risk individuals, while preserving the availability of an effective and low-cost medicine for the broader population.